Diagnosis and Treatment of Golfer's Elbow: A Review of Therapeutic Approaches - Dzwonnik, Karol; Zelik, Urszula; Florczak , Wojciech; Śnieżna, Joanna; Dziewic, Jakub; Domino, Wiktoria; Trestka, Gabriela; Przygoda, Maria; Włodyka, Jagienka; Stępień, Kamila; Adamczyk, Sabina (Quality in Sport, 2025)
Introduction: Medial epicondylitis, or golfer's elbow, is caused by repetitive stress on the medial epicondyle tendons, leading to pain, reduced grip strength, and limited mobility. Poor biomechanics and overloading worsen the condition, which involves tendon degeneration and inflammation. Treatment begins with rest, physical therapy, and NSAIDs, while advanced cases may require injections, surgery, or innovative therapies targeting oxidative stress. Aim of study Objective: The objective of this paper is to analyze the causes, symptoms, and available treatment n methods for golfer's elbow (medial epicondylitis). The paper aims to compare the effectiveness of conservative methods and surgical interventions in treating this condition, as well as discuss the latest advancements in therapy State of Knowledge: Medial epicondylitis, or golfer's elbow, is a chronic tendon condition caused by repetitive stress. Diagnosis relies on clinical evaluation and imaging, while treatment begins with conservative methods like rest and physical therapy. For resistant cases, surgical options and innovative therapies. A multimodal, personalized approach ensures optimal recovery and long-term relief. Summary (Conclusion): Medial epicondylitis, or golfer's elbow, is caused by repetitive stress and degenerative changes in the flexor-pronator tendons. Effective diagnosis combines clinical evaluation and imaging. Conservative treatment, including rest, physical therapy, and pharmacological support, is the first-line approach. In refractory cases, surgical options like open repair and arthroscopy, along with innovative techniques such as collagen-augmented sutures and stem cell applications, show promising results. Complementary therapies, such as ESWT, PRP, and manual therapy, further enhance outcomes, particularly in chronic cases. A multimodal, personalized approach ensures optimal tendon healing, functional recovery, and long-term symptom relief.